If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-9f=-10f+18
We move all terms to the left:
-9f-(-10f+18)=0
We get rid of parentheses
-9f+10f-18=0
We add all the numbers together, and all the variables
f-18=0
We move all terms containing f to the left, all other terms to the right
f=18
| 6x-3=3+4x+9 | | 3(x+1)+3x=-3(x-1)+3 | | 7x÷5x-7=21÷10x | | 9(3n-4)=(8n+8)+1 | | 200+.25m=360 | | 3x+36=9x-24 | | 15=v/13 | | -y-39=19 | | 30+x=-6(10x-5) | | 50x+2=7.50 | | 5.5(2x+11)=-5.5x+63.25 | | 294=14h | | 12x+1+92=25x+2 | | X+x-46+1/2x+x-35=360 | | -20+7c=20+12-6c | | 12x1+92=25x+2 | | 15(2x+2)=10(3x+4 | | -4b-2b=-6b+8 | | 4(5+x)/3=20 | | 1/3t-8=-6 | | 5/8g=3 | | 8x+4x+4x+8=11 | | 72-3y=100 | | -5(x-5)-10=-5x-10 | | 9=-8s-7 | | -60=4x | | 8−4j=–3j | | -2/5a=-18 | | 8−9z=–6z−10 | | 2(x-4)+4x=10x | | 19u-17=15u-1 | | h-8=67 |